(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the frequency, gender and causes of medico-legal deaths autopsied at Abbasi Shaheed Hospital in Karachi. Study Design: Retrospective study. Place and Duration of Study: This study was conducted at the Abbasi Shaheed Hospital from January 2018 till December 2019. Materials and Methods: This is a case study, involving the medico-legal deaths autopsied at Abbasi Shaheed Hospital. A detailed and complete autopsy was conducted in each case including both an external and an internal examination. The results were collected from the concerned authority on a structured Performa and analyzed statistically using SPSS version 15. Results: A total 956 autopsies were conducted during the two years period at Abbasi Shaheed Hospital. Among all the causes, road traffic accidents were the most common cause of death followed by firearms, hanging, fall, electric current, other asphyxia causes and assault. Majority of the victims were male with male to female ratio of 8:1. Conclusion: Road traffic accidents were the most common cause of death accounting for 42.25% of the total, followed by firearms which accounted for 24.5%, hanging accounted for 3.5% while fall accounted for 3.03%), electric current accounted for 2.71%, asphyxia was responsible for 2.19% of the total and assault accounted for 2.09%. The male to female ratio was 8:1 with 88.9% of victims being males. Victims belonged to the age group 21-30 years displaying the highest number (29.39%) of affection.